Pd Doped on TCH@SBA-15 Nanocomposites: Fabrication and Application as a New Organometallic Catalyst in the Three-Component Synthesis of N-Benzo-imidazo- or -thiazole-1,3-thiazolidinones - Kalhor, Mehdi; Dadras, Akbar (Frontiers in Chemistry, 2021)
In this project, the synthesis of a new Pd(II)/TCH@SBA-15 nanocomposite is described by grafting of 3-chloropropyltriethoxysilane (CPTES) and thiocarbohydrazide (TCH) on SBA-15 and subsequent deposition of palladium acetates, through the ligand-metal coordination method. The structure and morphology of this nanoporous was thoroughly identified using FT-IR, FESEM, TEM, EDX, XRD, TGA, AAs and BET instrumental analyses. In the following, its catalytic performance in the three-component synthesis of 3-benzimidazolyl or benzthiazoleyl-1,3–thiazolidin-4-ones via reaction of 2-aminobenzimidazole or 2-aminobenzothiazole, aromatic aldehydes and thioglycolic acid in acetone-H2O and under green conditions was considered. Thus, a new and effective procedure for the green synthesis of N-heterocyclic thiazolidinediones was obtained with advantages such as the use of a safe and recyclable organometallic nanocatalyst, short reaction time, easy purification process, good to excellent yield, non-toxic solvent and ambient temperature.